Efficient signcryption scheme based on Cocks’ identity cryptosystem - Changgen PENG; Xiaoyu ZHANG; Hongfa DING; Shanhui YANG (Tongxin xuebao)
Most of the existing identity-based signcryption schemes are based on bilinear or multilinear pairing operations construction.To solve the problem of low efficiency caused by complex pair operation, a new efficient signcryption scheme based on the identity cryptosystem of Cocks was proposed.Firstly, the security model of the proposed scheme was formalized, and the definition of confidentiality and unforgeability was given.Secondly, the quadratic residue problem was used to realize the concrete construction of the proposed scheme, and the signature algorithm was designed in a logical step by combining Jacobi symbol operation.Finally, the security proofed that the scheme satisfied the confidentiality and unforgeability was given under the random prediction model.The efficiency analysis shows that compared with the existing identity-based signcryption scheme, the proposed scheme greatly improves the computing efficiency and has good characteristics of identity-based cryptosystem.